2012
DOI: 10.1155/2012/426803
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms and 24-Hour Ambulatory Blood Pressure in Africans: The SABPA Study

Abstract: Disturbances in circadian rhythm might play a central role in the neurobiology of depression. We examined the association between depressive symptoms and 24-hour ambulatory BP in a sample of 405 (197 black and 208 Caucasian) urbanized African teachers aged 25 to 60 yrs (mean 44.6 ± 9.6 yrs). Depressive symptoms were assessed using the self-administered 9-item Patient Health Questionnaire (PHQ-9). After adjusting for age, sex, and ethnicity, participants with severe depressive symptoms (PHQ-9 ≥ 15) had higher o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 38 publications
(37 reference statements)
0
11
0
Order By: Relevance
“…While not yet shown in adolescents, three studies of older adult populations have revealed higher nocturnal BP levels and smaller BP decline in those experiencing high levels of depressive symptoms (Hamer et al, 2012;Scuteri, 2009;Watanabe et al, 2002). This suggests that depressive symptoms have a negative effect on the cardiovascular system during sleep.…”
Section: Introductionmentioning
confidence: 99%
“…While not yet shown in adolescents, three studies of older adult populations have revealed higher nocturnal BP levels and smaller BP decline in those experiencing high levels of depressive symptoms (Hamer et al, 2012;Scuteri, 2009;Watanabe et al, 2002). This suggests that depressive symptoms have a negative effect on the cardiovascular system during sleep.…”
Section: Introductionmentioning
confidence: 99%
“…13,19,20 These factors, plus smoking, account for around 90% of myocardial infarction in African populations, with a history of hypertension seeming to exert a more prominent effect in black Africans. Moreover, they are less likely to have their blood pressure controlled when on medication and have an increased prevalence of undiagnosed hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…13 Given the paucity of multi-ethnic data examining ABPM and the MBPS calculated using this novel approach, we postulated that the power of the morning surge and rate of morning rise in blood pressure will be different in black and white participants. 13 Given the paucity of multi-ethnic data examining ABPM and the MBPS calculated using this novel approach, we postulated that the power of the morning surge and rate of morning rise in blood pressure will be different in black and white participants.…”
mentioning
confidence: 99%
“…Numerous studies of depression have shown its association with HTN (Artinian, Washington, Flack, Hockman, & Jen, 2006;Davidson, Jonas, Dixon, & Markovitz, 2000;Hamer et al, 2012;Jonas & Lando, 2000;Reiff, Schwartz, & Northridge, 2001;Wu, Prosser, & Taylor, 2010), particularly for Blacks (Davidson et al, 2000;Jonas & Lando, 2000;Pickering, 2000). Depression can lead to HTN (Charlson, Stapelberg, Baxter, & Whiteford, 2011;Pickering, 2001a), and HTN can exacerbate depression (Centers for Disease Control and Prevention, 2010;Chapman, Perry, & Strine, 2005;Pickering, 2000).…”
Section: Link Between Depression and Hypertension (Htn)mentioning
confidence: 99%
“…Individuals who demonstrate an inability to handle stress tend to suffer more from depression (Dragan & Akhtar-Danesh, 2007). Also, research suggests that depression may predispose an individual to HTN (Centers for Disease Control and Prevention, 2010;Hamer et al, 2012;Jonas & Lando, 2000;McEwen, 2005;Pickering, 2001a;Schneider et al, 2001;Wu et al, 2010).…”
Section: Stressors and Copingmentioning
confidence: 99%